THE OFFICE OF SUSTAINABLE DEVELOPMENT - Yermekova, Gulzhan (Sustainable Development Office, Nazarbayev University, 2022)
The Office of Sustainable Development – established in 2018, as the consequence of Green Campus movement. The GC Concept is based on principles of the Sustainable Development concept: environmental, economic and social aspects. Green Campus – is an bottom-up initiative of the NU in order to make our University sustainable and green. Integration of the University’s core misssion: education research innovation
Keywords: Type of access: Open Access; Green Campus Office; Office of Sustainable Development; environment; green; Climate Change